Globulin expression in grain of Australian hard wheat cultivars is affected by growth environment - Md Zin, Noor Hasniza; Les, Copeland; A Wilkes, Meredith (AACC International, 2014)
Our aim was to study changes in wheat proteomes across different growth locations as the first step in linking protein composition with functional changes in grains produced using commercial production systems. Soluble and insoluble proteins were extracted sequentially from grain of three commercial wheat cultivars grown at four locations in New South Wales, Australia during a single season. Bands were separated using SDS-PAGE and identified by peptide mass fingerprinting. Quantitative changes in the electrophoretic patterns were observed mainly in the insoluble polypeptides of molecular mass between 40 – 70 kDa for all three cultivars grown at two of the four locations. These proteins were identified as mainly globulin and serpin isoforms, and triticin. Other proteins with changed expression included disease-resistance proteins, class III peroxidase, starch branching enzyme I, β-amylase, and storage proteins. Two-dimensional electrophoretic analysis was performed on two of the same wheat cultivars grown at one of the locations during two consecutive seasons. Protein spots that varied between seasons consisted of globulin and serpin isoforms, triticin, HMW-glutenin, gamma-gliadin, starch branching enzyme IIb and alpha amylase. The implications of the upregulation of globulin and triticin on whole meal flour quality, through their participation in polymerization of the gluten network, are considered.